Big data management: The case of Mulino Bianco's engagement platform for value co-creation. (5th April 2018) - Troisi, Orlando; D'Arco, Mario; Loia, Francesca; Maione, Gennaro
In the past few years, an explosion of interest in big data has occurred from both academia and business communities. To reduce the uncertainty associated with some types of big data, organizations can adopt specific strategies inspired by service-dominant logic and value co-creation between organizations and customers. Specifically, alternating the extant body of literature and the results emerged from the case–study analysis of Mulino Bianco's 'Nel mulino che vorrei', this research illustrates how different organizations can purposefully design particular engagement platforms for 'joint agential experiential creation' of big data and how organizations design digital and interactive environment in order to acquire and manage integrated, cleaned, trustworthy and efficiently accessible data for decision-making or product innovation activities. From a theoretical viewpoint, this basis model for joint agential experiential creation of big data advances the extant research offering a useful insight to reduce data veracity. From a practical perspective, this study explains why organizations should invest in engagement platforms, such as digital forum, social media brand pages or specific digital and interactive environment built for the occasion, to facilitate the collection, storage and the analysis of customer-generated big data.